Effect of Co-administration of Glibenclamide and Aqueous Calyx Extract of Hibiscus Sabdariffa on Oxidative Stress Markers in Streptozotocin-Induced Diabetic Rats (Nigerian Journal of Physiological Sciences, 2021)
The hyperglycaemia of diabetes mellitus (DM) induces oxidative stress which damages the tissues. Glibenclamide, an oral hypoglycaemic drug used in the treatment of DM has associated side effects. Natural products are considered safe in the treatment of chronic diseases. Hibiscus sabdariffa (HS) is a plant that has demonstrated antidiabetic activity. We aimed to determine the potential benefits of co-administration of HS and glibenclamide in ameliorating oxidative stress in streptozotocin (STZ)-induced diabetic rats.  A total of 25 male albino Wistar rats were divided randomly into five groups: control (Non-DM), diabetic (DM), diabetic treated with 600µg/kg BW of glibenclamide (DM + GLIB), diabetic treated with 500mg/kg BW of HS (DM + HS), diabetic treated with both 600µg/kg BW of glibenclamide and 500mg/kg BW of HS (DM + GLIB + HS). The interventions were administered for a period of 28 days. The Non-DM rats were significantly heavier (p